Perbaikan Manajemen Reproduksi Kambing Peranakan Etawah Melalui Sosialisasi dan Pelatihan kepada Kelompok Ternak Subur Kokap Kulon Progo DIY - Muhammad Rosyid Ridlo (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
Reproduction management Socialiszation to “Subur” Perananakan Etawah (PE) Goat Farmer Comunitee in Hargo Tirto, Kokap, Kulon Progo, Yogyakarta was focused on reproduction problems in PE Goat. The main issue that should be priority is Goat Reproduction. Good Dairy goat management reproduction will give positive effect to success of milk production. The back ground of animal husbandary comunitee is located in mountain range of Kulon Progo, their main job activity are as a coconut sugar farmer. The Subur Animal Husbandary Comunitee is grouped as a new dairy goat farmer. They still trying to learn how to develop their husbandary, do not have adequate knowledge of good management farming and good information about reproduction.  That condition are the reasons to choose Subur Animal Husbandary Comunitee as a target for Socialiszation in presentation and discussion to farmers. Specific explanation and direct practice in field and does oestrus observation. Distribution of feed, medicine, vitamin and mineral were given to Subur Animal Husbandary Comunitee. The results of this program give many positive impact to the farmers and dairy goats such as; the farmers understand and be able to detect signs of oestrus which is very important to them, the farmers have apply detection of oestrus by visual and buck as a natural oestrus detector, natural mating and pregnant occurrence increased after the farmers have applied oestrus detection in does of PE Goat.